Social interaction, social theory and work-related activities - Sarangi, Srikant (Calidoscópio, 2021)
Workplaces are constituted in socially embedded communicative practices. When interpreting work-related activities, workplace researchers have to trade carefully between micro-level social interaction and macro-level societal (trans)formation. On both fronts, they are positioned as outsiders to the dynamics of activities under study, although over time and with involvement they may become more integrated and accepted within a given community of practice, thus aligning themselves with participants’ perspectives. In this paper, I revisit the interrelationship between social structure and social interaction and propose a method of activity analysis as a way for studying workplace communication in practically relevant ways. At the same time, I suggest that the talk and text that are available for observation and analysis do not embody the entirety of the workplace ethos. Key words: knowledge/expertise, professional-client encounters, activity analysis.